Study of solar power plants as an aerator driver based on the Internet of Things (IoT) - Margana, Margana; Wahyono, Wahyono; Hermawan, Baktiyar Mei; W, Wiwik Purwati; Suwarti, Suwarti; Aulia, Nur Fatowil; Solikhin, Akhmad Riadzus (Politeknik Negeri Semarang, 2023)
The use of solar power plants is now developing, for example aerator drives with the Internet of Things. The purpose of designing aerators with the Internet of Things is to utilize programming instructions that each command can generate interaction with fellow devices and connect automatically without user intervention, even remotely. This research method begins with the study of literature, manufacture, installation of components, as an analysis carried out testing and data collection. The results of the tests conducted on day 5 include, the best solar radiation intensity power of 886.786 W/m2, the power produced by solar cells of 473.099 W and aerator power of 75.843 W, solar panel efficiency of 14.749%. and PLTS system efficiency of 4.275%. In this test, it was found that the addition of aeration can increase oxygen concentration and pH value of water. Keywords- Aerator, PLTS, Performance